Pemanfaatan Potensi Lokal Desa Tritunggal Sebagai Penunjang Sumber Belajar IPS Kelas VII Mts Ma’arif 23 Infarul Ghoy Tritunggal Lamongan - Rikza Syahrul Ramadhan; Bagus Setiawan (Pusat Riset dan Inovasi Nasional, 2023)
. Utilization of local potential in the form of convection textile industry centers as a source of learning with the aim that learning can also take advantage of environmental aspects. the local potential of Tritunggal Village, namely the center of the textile convection industry. can increase the potential of students as an effort to develop themselves The purpose of this study is to: (1) To describe the potential of Tritunggal Village which is used as a social studies learning resource on economic activity material at Mts Ma'arif 23 Infarul Ghoy Tritunggal Lamongan (2) To describe social studies learning process on economic activity material at Mts Ma'arif 23 Infarul Ghoy Tritunggal Lamongan (3) To describe the utilization of local potential in Tritunggal Village as a support for social studies resources at Mts Ma'arif 23 Infarul Ghoy Tritunggal Lamongan This research uses a type of research approach descriptive qualitative. Data collection techniques used in this study are observation, interviews, and documentation. In analyzing the data using data reduction, data presentation, drawing conclusions, and the validity of the results from the Tritunggal Village research, Tritunggal Village has local potential in the form of a textile convection industry center, which is in line with economic activities in the area. Utilization of local potential as a support for social studies learning at Mts Ma'arif 23 Infarul Ghoy Tritunggal Lamongan, increasing student involvement, enthusiasm for learning, insight, and social attitudes Social studies learning by utilizing local potential runs smoothly and effectively.